1980
DOI: 10.1524/zkri.1980.153.14.89
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of β-SnF2

Abstract: The crystal structure of ß-SnF 2 was refined from single crystal neutron diffraction data: Space group C2/c (monoclinic), a = 13.359(3)Â, b = 4.9099(6), c = 13.790(3)Â, β = 109.11(0.02)°. The structure consists of four Sn 4 F 8 tetrameres per unit cell held together by Van der Waals forces. Within the tetrameres we have covalent bonding, in agreement with measurements of the elastic and thermoealstic properties. The coordination of the tin atoms is a SnF 3 trigonal pyramid. Average Sn-F distances in the pyrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Thus, we may hope to see them « isolated » in dipolar experiments if the linewidths are not too large. 4. Verification of the assignments by comparison with dipolar results.…”
mentioning
confidence: 99%
“…Thus, we may hope to see them « isolated » in dipolar experiments if the linewidths are not too large. 4. Verification of the assignments by comparison with dipolar results.…”
mentioning
confidence: 99%
“…The first of these peaks has a δ iso value close to that of BaF 2 (−14.2 ppm), where fluoride ions occupy Ba 4 -coordinated tetrahedral sites. The second peak aligns with the average δ iso value of α-SnF 2 (−46 ppm), in which fluorine is triply coordinated with short Sn–F distances . Based on these comparisons, we assign these features at −14 and −45 ppm to broadly Ba-rich and Sn-rich fluorine environments, respectively.…”
Section: Resultsmentioning
confidence: 61%
“…The second peak aligns with the average δ iso value of α-SnF 2 (−46 ppm), 136 in which fluorine is triply coordinated with short Sn−F distances. 137 Based on these comparisons, we assign these features at −14 and −45 ppm to broadly Ba-rich and Sn-rich fluorine environments, respectively. The assignment of fluorine environments into broadly two types is qualitatively consistent with the computational fluoride-ion density data (Figure 6), where we observe quite different fluoride-ion densities in Ba-rich versus Sn-rich regions of our simulation model.…”
Section: T H I S C O N T E N T Imentioning
confidence: 96%
“…The birefringences of SnX 2 (X=F, Cl), SbX 3 (X=F, Cl), and Sn 14 O 11 Br 6 were investigated by Pan, et al., and all of them exhibit the 3D network constructed by Sn 2+ or Sb 3+ ‐centered polyhedra [119–128] . The millimeter‐sized α ‐SnX 2 was grown via slow evaporation of the solution at ambient temperature [123] .…”
Section: Resultsmentioning
confidence: 99%
“…The birefringences of SnX 2 (X = F, Cl), SbX 3 (X = F, Cl), and Sn 14 O 11 Br 6 were investigated by Pan, et al, and all of them exhibit the 3D network constructed by Sn 2 + or Sb 3 + -centered polyhedra. [119][120][121][122][123][124][125][126][127][128] The millimeter-sized α-SnX 2 was grown via slow evaporation of the solution at ambient temperature. [123] Meanwhile, they reported that the stereochemically active and arrangement of lone pairs on Sn 2 + and Sb 3 + make α-SnF 2 , SnCl 2 , SbF 3 , SbCl 3 , and Sn 14 O 11 Br 6 exhibit various optical anisotropy, the calculated birefringence is 0.191, 0.210, 0.104, 0.173 and 0.265@546 nm, respectively.…”
Section: Sn II or Sb Iii Cooperated With Non-π-conjugated X à (X = F ...mentioning
confidence: 99%